Green Surfactant: Synthesis of Sulfonate Surfactants Using Strecker Modification Techniques and Surfactant Formulation for Chemical Enhanced Oil Recovery (Ceor) Applications - Ilham ardatul putra; Yudha Taufantri; Yani F. Alli; Dadan Damayandri; Yohanes B.D. Wangge; Didin Mujahidin (Testing Center for Oil and Gas LEMIGAS, 2025)
Despite the continuing development of sustainable sources of energy, crude oil and natural gas resources remain crucial elements of the international economy. With global petroleum and liquid fuel demand continually increasing, improving the efficiency of extraction from existing natural reserves of petroleum is of utmost importance as the world gradually transitions away from fossil fuels toward more sustainable sources. Toward that end, enhanced oil recovery (EOR) techniques have been developed and are used to minimize the amount of crude oil and petroleum that is left behind in underground reservoirs from conventional drilling extraction methods. In this study, surfactants were synthesized using a fatty acid derived from palm oil as a hydrophobic group and sulfonat as a hydrophilic group. The use of vegetable oil as the raw material is likely due to its abundance and environmentally friendly. Sulfonation of anionic surfactant was performed by utilizing the Strecker modification technique in which an alkali metal bisulfite (versus sulfite) is used to sulfonate the epoxide group. The preferred sulfonating reagent is a mixture of sodium bisulphite and sodium sulfite (1:1; 1:2; 1:2.5) as well as various time reactions. Product surfactant was characterized by thin-layer chromatography (TLC) to determine the optimum condition and reaction conversion. The molecular structure of surfactant was confirmed by 1H NMR. Nonionic surfactant was then analyzed by measuring the interfacial tension (IFT) of oil and water, wettability, and imbibition test. The results showed that the optimum conditions to obtain the hight convertion were achieved by reacting oleil glisidil ether and Sodium Sulfite-Bisulfit at an equivalent mole ratio of 1: 2 and 21 hours’ reaction time. Oleil Glisidil Eter Sulfonat surfactant was able to decrease the IFT of oil and water as 10-2 dyne/cm in brine salinity condition of 18000 ppm and oil 34,39 OAPI. This study also formulated surfactants OGES and OGEP so that the IFT was up to 10-3 and the recovery factor from the imbibition test was up to 75% Rf. The results were then used to design the synthesis of vegetable surfactant oil with various carbon chain lengths and functional groups as an EOR surfactant hydrophobic group.